2001
DOI: 10.1177/088626001016004002
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Alcohol Expectancies and Alcohol Consumption Among Sexually Victimized and Nonvictimized College Women

Abstract: The present study investigated alcohol expectancies, alcohol consumption, sexual assertiveness, and the number of consensual sexual partners as potential risk factors for sexual assault among three groups of college women: nonvictimized, moderately victimized, and severely victimized. Women with severe victimization histories (attempted or completed rape), compared with nonvictims, reported more consensual sexual partners, less perceived assertiveness in their ability to refuse unwanted sexual advances, greate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
117
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(129 citation statements)
references
References 25 publications
9
117
3
Order By: Relevance
“…Consistent with a self-medication theory, women may be more motivated than men to consume alcohol out of response to stress (Greenfi eld et al, 2010). Available cross-sectional research assessing the impact of prior violence victimization on women's problem drinking supports a self-medication model (Corbin et al, 2001;Ullman et al, 2006). Evidence for a self-medication model is bolstered by longitudinal studies reporting associations between prior victimization and future alcohol use directly (Kilpatrick, 1997;Thompson et al, 2008;Widom et al, 2006) and indirectly through mood disorders such as MDD, a psychiatric consequence shared by many victims of violence (Clark et al, 2003;Golding, 1999;Madruga et al, 2011).…”
mentioning
confidence: 69%
“…Consistent with a self-medication theory, women may be more motivated than men to consume alcohol out of response to stress (Greenfi eld et al, 2010). Available cross-sectional research assessing the impact of prior violence victimization on women's problem drinking supports a self-medication model (Corbin et al, 2001;Ullman et al, 2006). Evidence for a self-medication model is bolstered by longitudinal studies reporting associations between prior victimization and future alcohol use directly (Kilpatrick, 1997;Thompson et al, 2008;Widom et al, 2006) and indirectly through mood disorders such as MDD, a psychiatric consequence shared by many victims of violence (Clark et al, 2003;Golding, 1999;Madruga et al, 2011).…”
mentioning
confidence: 69%
“…It is possible that the increased alcohol use, and resulting consequences, following incapacitated rape may just be an example of coping to regulate negative affect (Cooper, Frone, Russell, & Mudar, 1995;Stewart, Pihl, Conrod, & Dongier, 1998). Both greater endorsement of tension reduction expectancies and greater alcohol consumption have been associated with sexual victimization in female college students (Corbin et al, 2001;Marx et al, 2000) and clinical samples (Simpson, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, heavy drinking may follow sexual assault as a means of coping with assault-related psychological distress (Grayson & Nolen-Hoeksema, 2005;Miranda, Meyerson, Long, Marx, & Simpson, 2002). Several studies have reported increased alcohol consumption and more drinking-related negative consequences in sexually assaulted college students as compared to their non-assaulted peers (Corbin, Bernat, Calhoun, McNair, & Seals, 2001;Larimer, Lydum, Anderson, & Turner, 1999;Marx, Nichols-Anderson, Messman-Moore, Miranda, & Porter, 2000). This relationship appears consistent across both male and female victims (Larimer et al, 1999).…”
Section: Drinking In Response To Sexual Assaultmentioning
confidence: 98%
“…Specifically, college women with a history of sexual victimization tend to more strongly endorse alcohol expectancies related to their greater vulnerability to sexual assault when drinking (Benson, Gohm, & Gross, 2007). Victims of substance-fueled sexual assault are also much more likely to consume alcohol, as well as subscribe to alcohol expectancies related to social and physical benefits (Corbin, Bernat, Calhoun, McNair, & Seals, 2001;Marx et al, 2000).…”
Section: Associations Between Drinking Behavior Alcohol Expectancy mentioning
confidence: 99%